2014
DOI: 10.12693/aphyspola.125.1163
|View full text |Cite
|
Sign up to set email alerts
|

Controlling of Transformation Temperatures of Cu-Al-Mn Shape Memory Alloys by Chemical Composition

Abstract: The CuAlMn shape memory alloys having various chemical compositions were prepared by arc melting method to control the phase transformation parameters. The phase transformation parameters and structural properties of the alloys were investigated by dierential scanning calorimetry and optic microscopy, respectively. The eects of the chemical composition on characteristic transformation temperatures, enthalpy and entropy values of CuAlMn ternary system were investigated. The characteristic transformation tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Moreover, Kožuh et al [33] pointed out that precipitation in CuAlMn produces a change in the chemical composition of the matrix. Indeed, it has been found that the CuAlMn alloy's phase transition temperatures are highly dependent on composition [34]. As a result, the bainite formation is responsible for the observed increase in phase transformation temperatures and the loss of the cryogenic feature.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kožuh et al [33] pointed out that precipitation in CuAlMn produces a change in the chemical composition of the matrix. Indeed, it has been found that the CuAlMn alloy's phase transition temperatures are highly dependent on composition [34]. As a result, the bainite formation is responsible for the observed increase in phase transformation temperatures and the loss of the cryogenic feature.…”
Section: Discussionmentioning
confidence: 99%
“…10 On the other hand, the Cu-based shape memory alloys are usually annealed in β-region at 800 or 900 °C to achieve preconditions for the formation of shape memory effect. 10,11 Canbay et al 12 mentioned that copper-based shape memory alloys…”
Section: Introductionmentioning
confidence: 99%